A situation analysis of children & women in Bhutan, 2006 - Black, Maggie, 1945-; Stalker, Peter; National Commission for Women and Children (Bhutan); UNICEF Bhutan (Thimphu : UNICEF, 2006)
Evaluation of the ground realities of child and women development; study conducted by UNICEF Bhutan in close collaboration of National Commission for Women & Children, Bhutan.
Includes bibliographical references (p. 83-85).
Keywords: Child development -- Bhutan -- Evaluation; Women -- Bhutan -- Economic conditions; Women -- Bhutan -- Social conditions